A diary of a polish architect and film maker from his travels to the west. Modern Italian architecture in the Polish documentaries dating back to the turn of the 1950s and 1960s - NADOLNY, Adam (2018)
At the end of the 1950s and the beginning of the 1960s, travelling to the Western countries was to a large extent limited for an average citizen of the socialist Poland. After the democratisation of the country in 1956 travelling options improved a bit, however, the Poles could not travel as freely as they do today. Polish architects could learn about the architecture of Western Europe mainly from such sources as the magazines and occasional travels. In the second half of the 1950s and the beginning of the 1960s, a documentary film became a new medium presenting modern architecture. This article shows how modern architecture of Italy presented in the documentary films of the turn of the 1950s and 1960s supplemented the knowledge of Polish architects on modern Europe in that period. The film image was, on the one hand, a form of a public diary from the travels and, on the other hand, a medium which recorded and preserved the images of places popular with tourists and showed these images to the Polish architects who were not allowed to travel there.